ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PERUSAHAAN CREDIT AGENCY SELAIN BANK DI BURSA EFEK INDONESIA UNTUK PERIODE TAHUN 2011-2015 - Ermaini Ermaini; Arniwita Arniwita (Universitas Batanghari, 2017)
This study aimed to determine the effect of profitability and dividend payout ratio of capital structure in the non-financial listed companies in Indonesia Stock Exchange in 2011-2015. In theory, determining the factors that affect the capital structure based on the pecking order theory. This study included 10 non-financial firms using quantitative research where research data is derived from secondary data obtained from a non-participant observation study documentation. Were treated with multiple linear regression techniques. The analysis showed that profitability significantly and negatively related to capital structure while the dividend payout ratio has no significant effect on capital structure.Keywords: capital structure, dividend payout ratio, profitability